(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2020)
Bioethanol has grown into a large business, and it seems that it will continue to grow in the foreseeable future. Although certain challenges, such as rivalry among bioethanol and human food, bioethanol is widely recognised as a sustainable and renewable new energy sources. Bioethanol has the potential to be a good source of basic raw materials. Dehydrating ethanol yielded ethylene, the most important organic biochemical raw material. Throughout WWII, as the petrochemical sector boomed, industrial ethanol was mostly produced through hydration of ethylene. Humans should expect bioethanol to become a new source of simple organic raw materials, and other higher-value fine and specialized chemicals, rather of merely a fuel, now that it has entrenched itself as a substantial fuel mixture. Each day, a slew of new bioethanol enterprises open their doors. More research into bio - ethanol as either a starting raw chemical source is needed.